Edible Landscaping for Urban Sustainability - Eva C. Worden (EDIS, 2004)
Landscaping in the urban setting offers tremendous opportunity for contributing to sustainability. One such opportunity is edible landscaping. Edible landscapes are those that include plant species for human consumption. This document is ENH971, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 2004.